DIMENSI PEMAKNAAN BUDAYA PADA PRINSIP KESOPANAN TINDAK TUTUR DALAM PERCAKAPAN MELALUI APLIKASI CHATTING - Ida Ayu Vivin Indah Sari S.; Ni Putu Mega Purnami; Jro Balian Meylani Eka Yanti (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2024)
This study aims to determine how the cultural dimension is able to influence the use of politeness maxims in speech acts used by speakers through messages sent on the Whatsapp chat application. Some messages sent and received through the Whatsapp application are the source of data in this study. Data collection methods and techniques used are documentation. Qualitative descriptive method is used to describe the results found in the data and explain them in more detail and in depth so as to find the red thread. The results of this study found 6 maxims of politeness found with 6 message data through the Whatsapp chat application, namely tact maxim, generosity maxim, approbation maxim, modesty maxim, agreement maxim, and sympathy maxim. Meanwhile, the cultural dimensions found in the use of these maxims are situational behavior, intraorganistic and extraorganistic.